C-reactive protein during pregnancy and in the early postpartum predicts adverse metabolic health outcomes at 1 year postpartum in women with gestational diabetes - Dan Yedu Quansah; Antje Horsch; Leah Gilbert; Marc Y. Donath; Jardena J. Puder; the MySweetheart research group (Cardiovascular Diabetology, 2023)
Abstract Background Women with gestational diabetes mellitus (GDM) have higher insulin resistance and/or reduced secretion, an increased risk of future diabetes and cardiovascular disease, which may be due to a pathological activation of the innate immune system. C-reactive protein (CRP) is induced by inflammatory cytokines and reflects innate immune activity. We investigated the prospective associations between CRP during the perinatal period with adverse metabolic outcomes at 1 year postpartum in women with previous GDM. Methods We analyzed data from the MySweetheart trial that included 211 women with GDM at 28–32 weeks gestational age (GA). CRP was measured during  pregnancy at 28-32 weeks GA, at 6–8 weeks and at 1 year postpartum. Metabolic outcomes at 1 year postpartum included weight, total and central body fat, measures of insulin resistance and secretion and presence of the metabolic syndrome (MetS). A 75 g oral glucose tolerance test was performed to measure glucose and insulin values every 30 min over 2 h to calculate indices of insulin resistance (MATSUDA, HOMA-IR) and of absolute (AUCins/glu, HOMA-B) and insulin resistance-adjusted insulin secretion (ISSI-2). Results CRP during pregnancy and at 6–8 weeks postpartum predicted increased weight, body fat and visceral adipose tissue (VAT), insulin resistance (higher HOMA-IR, lower MATSUDA), absolute insulin secretion (HOMA-B, AUCins/glu), a reduced adjusted insulin secretion (ISSI-2) and a higher prevalence of the MetS at 1 year postpartum (all p ≤ 0.036). These relationships particularly those concerning CRP during pregnancy, were independent of weight ( for VAT, insulin resistance and secretion indices, MetS; all p ≤ 0.032) and of body fat ( for VAT, MATSUDA, MetS; all p ≤ 0.038).  Conclusion CRP during pregnancy and in the early postpartum predicted an adverse cardio-metabolic profile in women with prior GDM at 1 year postpartum independent of weight. The prospective association of CRP with increased insulin resistance and reduced adjusted insulin secretion hint to the role of inflammation in the development of impaired metabolism after GDM and could be used as an early marker for risk stratification.